Ethereum blockchain for electronic health records: securing and streamlining patient management - Mole, J. S. Simi; Shaji, R. S. (Frontiers in Medicine, 2024)
Electronic health records (EHRs) are increasingly replacing traditional paper-based medical records due to their speed, security, and ability to eliminate redundant data. However, challenges such as EHR interoperability and privacy concerns remain unresolved. Blockchain, a distributed ledger technology comprising connected, encrypted data blocks, presents a promising solution. This study explores how Blockchain technology can revolutionize hospital EHR management. Our proposed solution securely transfers medical records between patients and doctors using the InterPlanetary File System (IPFS) and the Ethereum platform. By utilizing Smart Contracts, it automates data transfers, ensuring patient anonymity and reducing computational complexity, while securely storing patient data on the network. Patient records are stored locally on the Ganache server, with the front end managed using HTML, CSS, ReactJS, and JavaScript, and the backend developed in Solidity. Experiments show that Blockchain technology combined with attribute-based access control ensures medical data's secure storage and integrity. The system's throughput increases linearly with the number of users and requests, enhancing the framework's efficiency and scalability. The minimum recorded latency is 14 ms.